2009
DOI: 10.1002/jcb.22339
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and coordinate downregulation of the NPC1 and NPC2 genes are associated with the sequestration of LDL‐derived cholesterol within endocytic compartments

Abstract: The Niemann-Pick C1 and C2 (NPC1 and NPC2) proteins have a central role in regulating the transport of lipoprotein-derived cholesterol from endocytic compartments to the endoplasmic reticulum for esterification by acyl-CoA:cholesterol acyltransferase (ACAT) and feedback inhibition of the sterol regulatory element-binding protein (SREBP) pathway. Since the NPC1 gene/protein has recently been shown to be downregulated by feedback inhibition of the SREBP pathway, the present study was performed to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…However, this sensitivity was only partial in the case of 3MA, pointing either to LAL-independent effects of autophagy that contribute to GSIS, or LAL working through other mechanisms in addition to lipophagy. The latter would be consistent with the role of LAL in mobilising lipids bound to lipoprotein [17,18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, this sensitivity was only partial in the case of 3MA, pointing either to LAL-independent effects of autophagy that contribute to GSIS, or LAL working through other mechanisms in addition to lipophagy. The latter would be consistent with the role of LAL in mobilising lipids bound to lipoprotein [17,18].…”
Section: Discussionsupporting
confidence: 81%
“…The generally excellent concordance between all these approaches suggests that lipophagy serves as a constitutive negative regulator of GSIS. It will be important in future studies to address how this role intersects with the better-known function of LAL in hydrolysing lipid from LDL [17,18]. Although the contribution of the amplification pathway to GSIS is now well established, the underlying mechanisms remain obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in fibroblasts have suggested that retention of cholesterol within lysosomal compartments may serve to protect cells from endoplasmic reticulum (ER) stress caused by an excess of FC in the ER membrane. Garver et al ( 2008 ) and Jelinek et al ( 2009 ) found that loading normal human fibroblasts with LDL results in reduced SREBP-dependent expression of NPC1 and NPC2. Jelinek et al ( 2012 ) reported that in a mouse model of diet induced obesity, dietary fatty acids but not cholesterol induced down regulation of NPC1 in both hepatic cells and peritoneal fibroblasts via feedback inhibition of the SREBP pathway.…”
Section: Indications Of a Lysosomal Cholesterol Trafficking Defectmentioning
confidence: 99%
“…The cholesterol needed for lipid raft formation and maintenance can be derived from exogenous sources such as lipoproteins, especially LDL, or from cellular synthesis via the mevalonate pathway in the ER followed by transport to the plasma membrane. 41, 97 Another source of cholesterol are intracellular lipid droplets. Movement of cholesterol out of lipid droplet relies upon extrinsic signals promoting the hydrolysis of CE by cholesterol ester hydrolases.…”
Section: Microdomain Cholesterol Regulation: the Role Of Effluxmentioning
confidence: 99%